Determination of the monetisation coefficient dynamics of the Russian economy and its impact on macroeconomic indicators - A. V. Berdyshev; D. K. Sopov (Вестник университета)
The monetisation coefficient is the most important indicator of the saturation level of the economy with money. This article examines the dynamics of the monetisation coefficient of the Russian economy in 2017–2021, provides a forecast for the level of monetisation for 2022, and an assessment of its impact on key macroeconomic indicators: unemployment, inflation and economic growth. Based on the correlation analysis, the existence of a strong relationship between the monetisation coefficient and the unemployment rate in Russia has been determined, while an increase in unemployment in the country contributes to a decrease in the gross domestic product, which, in turn, is an important component in calculating the monetisation level. A direct linear relationship between the monetisation level and gross domestic product has been revealed. The existence of a direct relationship between the level of inflation and the monetisation of the Russian economy has been determined. The conclusion is made about the need to increase the monetisation level of the Russian economy.